Penerapan Asas Mutakhir Dalam Pemeliharaan Data Pendaftaran Tanah Pada Badan Pertanahan Nasional Kabupaten Sragen - Himawan Ardi Nugroho; Wida Astuti (Jurnal Discretie, 2020)
This study aims to determine the application of maintenance of land registration data based on Government Regulation Number 24 of 1997 concerning Land Registration. Updating of land registration data must be registered by the right holder concerned if there is a change in the land parcel concerned. The author conducted this research at the Sragen Regency. In organizing the maintenance of land registration data, it is carried out by the National Land Agency of Sragen Regency. In addition, there is a role for the Land Deed Making Official to make an authentic deed to prove legal events that have been committed by the parties to a land parcel so that there is sufficient data completeness for registration. This activity aims to ensure that the rights holders concerned have legal certainty and there is orderly land administration. This legal research uses normative juridical research with prescriptive research characteristics. This research approach uses a statutory approach. Legal materials used in this research are primary legal materials in the form of statutory regulations, secondary legal materials in the form of works of academics, scientists or legal practitioners, and supported by non-legal materials in the form of interviews with National Land Agency employees. The results of this research are the first is the application of the latest principles in the National Land Agency of Sragen Regency has met the latest principles because it is evident from the data maintenance activities that there are no public reports of errors in changes and the second is the laws and regulations governing land registration. reflects current principles because the articles governing data require up-to-date data and the obligation for the holder of the land rights concerned to register changes